Hidrolisa Enzymatik pada Serat Selulosa - Indah Molektuz Zuchairah (Teknoin, 2005)
Sellulose material such as cotton, linen, ramie and viscose rayon fabrics along with a cotton/linen blend were hydrolyzed with cellulase from trichoderma viride. Surface fibrils were eliminated by 6 hour treatment in all cases. The loss of fibrillar matter appeared to be the primary cause of weight loss at this stage. On prolonged treatment, cotton, lines, and viscose rayon lost weight at a faster rate than ramie and the cotton/linen blend. The fall in yarn strength was progressive with increasing weight loss for cotton and viscose, while for linen and ramie it was slight initially and then increased sharply. Retention of strength after 46 hours incubation time increased in the order ramie